New Pathogenesis Mechanisms and Translational Leads Identified by Multidimensional Analysis of Necrotizing Myositis in Primates - Priyanka Kachroo (American Society for Microbiology, 2020)
ABSTRACT A fundamental goal of contemporary biomedical research is to understand the molecular basis of disease pathogenesis and exploit this information to develop targeted and more-effective therapies. Necrotizing myositis caused by the bacterial pathogen Streptococcus pyogenes is a devastating human infection with a high mortality rate and few successful therapeutic options. We used dual transcriptome sequencing (RNA-seq) to analyze the transcriptomes of S. pyogenes and host skeletal muscle recovered contemporaneously from infected nonhuman primates. The in vivo bacterial transcriptome was strikingly remodeled compared to organisms grown in vitro, with significant upregulation of genes contributing to virulence and altered regulation of metabolic genes. The transcriptome of muscle tissue from infected nonhuman primates (NHPs) differed significantly from that of mock-infected animals, due in part to substantial changes in genes contributing to inflammation and host defense processes. We discovered significant positive correlations between group A streptococcus (GAS) virulence factor transcripts and genes involved in the host immune response and inflammation. We also discovered significant correlations between the magnitude of bacterial virulence gene expression in vivo and pathogen fitness, as assessed by previously conducted genome-wide transposon-directed insertion site sequencing (TraDIS). By integrating the bacterial RNA-seq data with the fitness data generated by TraDIS, we discovered five new pathogen genes, namely, S. pyogenes 0281 (Spy0281 [dahA]), ihk-irr, slr, isp, and ciaH, that contribute to necrotizing myositis and confirmed these findings using isogenic deletion-mutant strains. Taken together, our study results provide rich new information about the molecular events occurring in severe invasive infection of primate skeletal muscle that has extensive translational research implications. IMPORTANCE Necrotizing myositis caused by Streptococcus pyogenes has high morbidity and mortality rates and relatively few successful therapeutic options. In addition, there is no licensed human S. pyogenes vaccine. To gain enhanced understanding of the molecular basis of this infection, we employed a multidimensional analysis strategy that included dual RNA-seq and other data derived from experimental infection of nonhuman primates. The data were used to target five streptococcal genes for pathogenesis research, resulting in the unambiguous demonstration that these genes contribute to pathogen-host molecular interactions in necrotizing infections. We exploited fitness data derived from a recently conducted genome-wide transposon mutagenesis study to discover significant correlation between the magnitude of bacterial virulence gene expression in vivo and pathogen fitness. Collectively, our findings have significant implications for translational research, potentially including vaccine efforts.